2020
DOI: 10.1016/j.berh.2020.101548
|View full text |Cite
|
Sign up to set email alerts
|

Implementing models of care for musculoskeletal conditions in health systems to support value-based care

Abstract: Models of Care (MoCs), and their local Models of Service Delivery, for people with musculoskeletal conditions are becoming an acceptable way of supporting effective implementation of value-based care. MoCs can support the quadruple aim of value-based care through providing people with musculoskeletal disease improved access to health services, better health outcomes and satisfactory experience of their healthcare; ensure the health professionals involved are experiencing satisfaction in delivering such care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 136 publications
(188 reference statements)
0
40
0
Order By: Relevance
“…KIs advocated for a strategy that targeted function through the adoption of high-value care and de-adoption of low-value care with reform priorities that are adaptable to local contexts in recognition of variability in economic development and health priorities across countries. These attributes align with the principles of developing system-level models of care and transformations needed to deliver high-value care in health systems [ 39 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…KIs advocated for a strategy that targeted function through the adoption of high-value care and de-adoption of low-value care with reform priorities that are adaptable to local contexts in recognition of variability in economic development and health priorities across countries. These attributes align with the principles of developing system-level models of care and transformations needed to deliver high-value care in health systems [ 39 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 77%
“…Further, we purposively sampled across clinical disciplines and from peak global and regional organisations. Valuable perspectives from consumer advocates and people with lived experience highlight the critical importance of person-centred viewpoints [ 58 ]. The logic model provides a data-driven and contemporary framework upon which a global strategy can be formulated.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons for excluding papers at full-text review were because they did not discuss a formal change management method explicitly (144), were not in a healthcare setting, 16 were commentary, protocol or editorial pieces, 11 or were not in health service delivery. 6 Many studies alluded to common concepts or techniques identified in change management methodologies but were excluded if no explicit model or framework was utilised. The distinct and expansive literature employing the Model for Improvement as a methodology was excluded because, whilst the model intersects with change management methodologies, the focus is determining the nature of changes and adaptations to introduce through incremental introduction and analysis of changes rather than the process of managing the change.…”
Section: Resultsmentioning
confidence: 99%
“…The most common reasons for excluding papers at full-text review were because they did not discuss a formal change management method explicitly (144), were not in a healthcare setting, 16 were commentary, protocol or editorial pieces, 11 or were not in health service delivery. 6 Many studies alluded to common concepts or techniques identified in change management methodologies but were excluded if no explicit model or framework was utilised.…”
Section: Excluded Studiesmentioning
confidence: 99%
See 1 more Smart Citation